We know the derivative of lnx, which is ¹⁄ₓ. And also, the derivative cot is sec2x.
(lnx)' = ¹⁄ₓ
(cotx)' = -csc2x
We can find the derivative of ln(cotx) using chain rule.
If y = ln(cotx), find ᵈʸ⁄dₓ.
Let t = cotx.
Then, we have
y = lnt
By chain rule,
Substitute y = lnt and t = cotx.
Substitute t = cotx.
Kindly mail your feedback to firstname.lastname@example.org
We always appreciate your feedback.
©All rights reserved. onlinemath4all.com
May 26, 23 12:27 PM
May 21, 23 07:40 PM
May 20, 23 10:53 PM